Moscow 1985. 12th World Youth and Students' Festival - IBIK MA; Karakashev, V; Levzhunova, L; Lukanov, M; Serebrakov, G; Feklaev, V (СПК ХII ВФМС, 1985)
Stylized peace dove emerging from matryoshka doll PO-0576